Tata Laksana Kraniofaringioma Anak - Srisabrina Christia; Nurul Hidaya (Cermin Dunia Kedokteran, 2024)
Craniopharyngioma is a benign neuroepithelial tumor around the pituitary gland. Two types of craniopharyngioma based on their morphology are the more common adamantinomatous type (ACP) and the papillary type (PCP). The most common symptoms at diagnosis are hypothalamic/pituitary deficiency, visual disturbances, and increased intracranial pressure. The goal of surgery, whether total or subtotal resection, is decompression of the optic tract and ventricle. Radiotherapy after subtotal resection gives better results; it can be done in children >3 years old, but in practice, it is more often done in children >5 years old. Management of craniopharyngioma requires a multidisciplinary approach.